2020
DOI: 10.30742/tpd.v2i01.888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pembelajaran Tematik Dengan Penilaian Autentik Di SDN Pasar Baru 1 Kota Tangerang

Abstract: Penelitian ini bertujuan untuk mendapatkan informasi yang komperehensip mengenai evaluasi pembelajaran tematik dengan menggunakan penilaian autentik di SDN Pasar Baru 1 Kota Tangerang. Hasil temuan sebagai berikut : pada kegiatan evaluasi belajar pembelajaran tematik dengan penilaian autentik penilaian nya menggunakan taksonomi bloom yang terdapat C1 sampai C6. Dalam pelaksanaan pembelajaran autentik tidak selalu berjalan mulus. Ada bebreapa kendala diantaranya yaitu dari aspek guru atau pengajarnya yang masih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In the Merdeka curriculum, the evaluation process uses diagnostic assessments, formative assessments, summative assessments, and projects. In the thematic learning of the 2013 curriculum, the teacher uses authentic assessments, namely knowledge, skills, and attitudes, which are divided into two spiritual attitude assessments (referring to the formation of piety and faith) and social attitudes (honesty, responsibility, tolerance, discipline, courtesy, cooperation, and confident) (Magdalena et al, 2021;Tiara & Sari, 2019). Furthermore, in the Merdeka curriculum, the teacher provides a non-cognitive diagnostic assessment by giving probing questions to students to identify student competence achievements, adapting classroom learning to average student performance, and providing improvement or additional learning for students whose performance is below average (Rahmansyah, 2021;Wiguna & Tristaningrat, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the Merdeka curriculum, the evaluation process uses diagnostic assessments, formative assessments, summative assessments, and projects. In the thematic learning of the 2013 curriculum, the teacher uses authentic assessments, namely knowledge, skills, and attitudes, which are divided into two spiritual attitude assessments (referring to the formation of piety and faith) and social attitudes (honesty, responsibility, tolerance, discipline, courtesy, cooperation, and confident) (Magdalena et al, 2021;Tiara & Sari, 2019). Furthermore, in the Merdeka curriculum, the teacher provides a non-cognitive diagnostic assessment by giving probing questions to students to identify student competence achievements, adapting classroom learning to average student performance, and providing improvement or additional learning for students whose performance is below average (Rahmansyah, 2021;Wiguna & Tristaningrat, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Then the results of the study [25] The findings indicated that the challenges faced by elementary school teachers in implementing the 2013 Curriculum were the teachers' difficulty in assessing students because in the 2013 Curriculum, assessments were conducted in accordance with each student's respective Basic Competencies, so it really took a long time to feel difficulty. Next inquiry how is your school's implementation of the Merdeka Learning curriculum going (Table 7)?…”
Section: Pgri 6 Palembang Junior High Schoolmentioning
confidence: 99%
“…Guru sudah mampu melaksanakan penilaian autentik secara menyeluruh. 31 Untuk mencapai kepuasan hasil belajar siswa tidak terlepas dari faktor siswa secara individu, artinya minat dan motivasi untuk belajar sangat dipengaruhi oleh siswa itu sendiri yang mengarah pada perubahan perilaku siswa dalam belajar. Perubahan tersebut perilaku ada yang bersifat positif seperti keiinginan untuk belajar, mengikuti kegiatan pembelajaran secara aktif dan melaksanakan setiap tugas-tugas yang diberikan.…”
Section: Pelaksanaan Penilaian Autentikunclassified